Photosynthetic acclimation to light of the three taxa of a Primula vulgaris x P. veris hybrid zone in the Bakony mountains - Medvegy, Anna; Kálmán, Katalin; Lehoczki, Endre (Acta Biologica Szegediensis, 2005)
The effects of light on the habitat choice of Primula vulgaris, P. veris and their spontaneous interspecific hybrids were studied. Photosynthetic performance (CO2 fixation) and composition of the photosynthetic pigments were measured on plants grown under semi-shaded conditions (control) and under natural high light condition for 20 days (HLG). Assimilation rates of P. veris were better than those of P. vulgaris at all light intensities. Hybrids photosynthesised similarly well as P. veris at lower light intensities, and presented intermediate photosynthetic performance between the parent species at higher light intensities. Total chlorophylls, chlorophyll a/b ratio, xanthophyll cycle pool, and the ratio of total carotenoids to total chlorophylls were higher in P. veris than in P. vulgaris, and these parameters, with the exception of the last one, showed considerable similarity of hybrids to P. vulgaris. Contrasting with the parent species, hybrid plants were able to increase the xantophyll cycle pool significantly after an intensive light exposure. The HLG treatment revealed that the extent of the photoinhibition was lower in P. veris than in the other two taxa. These results explain the difference between the habitat preferences of the parent species, and the ability of hybrids to occupy more open sites than P. vulgaris can.